2019
DOI: 10.1002/vms3.208
|View full text |Cite
|
Sign up to set email alerts
|

Foot and mouth disease outbreak investigation and estimation of its economic impact in selected districts in northwest Ethiopia

Abstract: Foot and mouth disease (FMD), a highly contagious and economically important disease of cloven‐hoofed animals, is endemic in Ethiopia. Foot and mouth disease outbreak investigation and follow‐up studies were undertaken to identify the causative serotype, determine the morbidity and mortality, and estimate the economic impact of the outbreaks in selected districts of Northwest Ethiopia. The serotype of FMD virus involved in the outbreaks was identified by antigen detection ELISA from clinical samples. Morbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Farmers in the urban market oriented system keep more productive but disease susceptible animals for market milk production, hence, would be sensitive to impact of FMD and it is economically rational that they were willing to pay more for the vaccine. In support of this an FMD economic impact study in the same areas indicated much higher loss of USD 459 (USD 26 per animal in the affected herd) due to FMD outbreak in a MO farms as compared to USD 34 (USD 5 per animal in affected herd) in CLM farms [30]. Willingness to pay was also higher for respondents whose main livelihood is livestock raising than respondents whose main livelihood is other than livestock.…”
Section: Factors Affecting Willingness To Paymentioning
confidence: 63%
“…Farmers in the urban market oriented system keep more productive but disease susceptible animals for market milk production, hence, would be sensitive to impact of FMD and it is economically rational that they were willing to pay more for the vaccine. In support of this an FMD economic impact study in the same areas indicated much higher loss of USD 459 (USD 26 per animal in the affected herd) due to FMD outbreak in a MO farms as compared to USD 34 (USD 5 per animal in affected herd) in CLM farms [30]. Willingness to pay was also higher for respondents whose main livelihood is livestock raising than respondents whose main livelihood is other than livestock.…”
Section: Factors Affecting Willingness To Paymentioning
confidence: 63%
“…In their study of FMD outbreak investigation and economic impact assessment in Ethiopia, [30] found that vaccinating animals decreased production losses due to the outbreak and increased animal production and productivity.…”
Section: Discussionmentioning
confidence: 99%
“…The virus can be transmitted either directly via contact with an infected host or indirectly via contact with a contaminated environment. In addition to contact virus can transmit to a new susceptible animal either orally or via the respiratory tract [16].…”
Section: Introductionmentioning
confidence: 99%